"Institutions Don't Hug People:" A Roadmap for Building Trust, Connectedness, and Purpose Through Photovoice Collaboration. (May 2021) - True, Gala; Davidson, Lawrence; Facundo, Ray; Meyer, David V.; Urbina, Sharon; Ono, Sarah S.
The Department of Veterans Affairs (VA) has recently increased support for inclusion of Veterans and family caregivers as collaborators on the research that affects them. In this article, the authors—two VA investigators, two Veterans, and two caregivers—draw from nearly a decade of participatory action research to highlight the methods we have employed to build and sustain collaboration. These methods include the following: using ethnographic approaches to engender trust, treating informed consent as an ongoing process, and sustaining engagement through shared dissemination of findings. We also consider impacts of engaged research that lie outside the parameters of what traditionally "count" as outcomes and that have helped us maintain our collaborative relationships even during periods between funding. We provide examples of how community engagement has bridged Veteran communities and VA, and how the use of visual and narrative methods of dissemination has led to social connectedness and repurposing of Veterans' and caregivers' mission as advocates. Our goal is to inform those who wish to conduct this type of research, to further pull research efforts in this direction, and to demonstrate the value of collaborative research from the point of view of those who have been engaged in it.